The Role of Motivation in Mediating Competence and Teaching Style Against Accounting Understanding - Sungguh Ponten Pranata; Ahmad Rivai; Ballian (Publisher Cv. Inara, 2021)
Understanding of accounting has an important meaning both for students and for universities. The purpose of this research is to determine the direct and indirect effect of competency variables and teaching style on accounting understanding through motivation. This type of research is classified as a cause-and-effect research where this research was conducted at STIE Mahkota Tricom Unggul. As for the target population and sample in this study, they are active in the 2019-2020 school year, amounting to 112 people. Where the sampling technique is quota sampling. Where the sample in this study amounted to 112 respondents. Furthermore, the data collection technique used a questionnaire which was distributed to all samples. The questionnaire measurement scale uses the Likert scale. The results showed that competency had a positive and significant effect on motivation. Teaching style has a positive and significant effect on motivation. Competence has a positive and significant effect on accounting understanding. Teaching style has no effect on students' accounting understanding at STIE Mahkota Tricom Unggul. Motivation has a positive and significant effect on student accounting understanding at STIE Mahkota Tricom Unggul. Motivation has no role in mediating competence in accounting understanding. However, motivation has a role in mediating the teaching style of accounting understanding.